On the insertion of non-etymological dental stops in Croatian - Pavao Krmpotić (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2015)
The paper deals with the insertion of the dental stops t and d in the history of the Croatian language. During the Proto-Slavic period, the non-etymological dental consonant t was inserted between s and r - this innovation can be defined as Proto-Slavic excrescence, since it was well-preserved in all Slavic languages. The best-known example of this sound change is the Proto-Slavic word *struja ‘stream’, whose cognates are the Lithuanian srauja ‘stream’, the Old Indic sravati, and the Greek ῥέω ‘to flow’. Proto-Slavic excrescence emerged after the satemisation of the Indo-European palatovelars, but prior to the metathesis of liquid resonants, which took place in the early ninth century. After the disintegration of the Proto-Slavic language, the same type of sound change occurred in some South Slavic dialects, including the Štokavian and Čakavian dialects of Croatian. The new South Slavic excrescence affected the consonant clusters sr, žr, and zr creating new forms of inherited lexemes, such as striješ ‘frost’ (< PSl. *seršь) and ždrijebe ‘foal’ (< PSl. *žerbę). Many of these lexemes are attested in Standard Croatian, and this paper attempts to properly explain their history and etymology.